Business Performance Model: The Role of Management Abilities and Entrepreneurial Character in Penta helix Coaching Collaboration - Slamet Mudjijah; Astrid Dita Meirina; Priyambada Bagus Artanta (Qubahan Academic Journal)
This research aims to reveal the impact of the Penta-Helix collaborative business coaching process on entrepreneurial character, management abilities, and business performance. The study used a quantitative approach. The population in this study was 250 active members of the Tangerang MSME community. The research sample was 150 MSMEs. Data was processed using SEM PLS software. The results indicate that coaching improves entrepreneurial character and management abilities but does not directly enhance business performance. This research proves that entrepreneurial character and Management Capability mediate the influence of coaching on business performance. This research provides theoretical implications for developing corporate resource-based strategic management theory, where external parties must mobilize company resources, which are the primary key to achieving business performance. The practical implications of the findings include how they can guide MSME coaching programs. Further research should explore whether collaborative business coaching can directly improve business performance.